Graphene quantum dots and their metallophthalocyanines nanoconjugates as novel photoluminescent nanosensors - Achadu, Ojodomo John (Rhodes University, Faculty of Science, Department of Chemistry, 2018)
The fabrication and application of graphene quantum dots (GQDs)-based photoluminescent probes for the detection of analytes is presented. GQDs were functionalized with complexes such as metallophthalocyanines (MPcs), metal nanoparticles (Au@Ag NPs), 2,2,6,6-tetramethyl(piperidin-1-yl)oxyl (TEMPO), maleimide and thymine for the sensing of target analytes such as ascorbic acid (AA), biothiols (cysteine, homocysteine and glutathione) and mercury ion (Hg²+). The design strategy and approach was based on the quenching of the fluorescence of the GQDs upon functionalization with the above-mentioned complexes, which could be restored in the presence of the target analytes (due to their specific interaction affinity with the complexes). For the detection of AA, GQDs were covalently and/or non-covalently conjugated to TEMPO-bearing complexes to form GQDs-4A-TEMPO and GQDs-TEMPO-MPc systems with nanomolar limits of detection. For the detection of biothiols, Au@Ag NPs and maleimide-bearing complexes (MPc), which have specific affinity to interact with biothiols, were deployed. Hg²+ detection involved the use of GQDs and/or MPcs with thiol and thymine groups, respectively. In addition, a smart sensing platform was designed for the dual detection of biothiols and Hg²+ using supramolecular hybrid of polyethyleneimine functionalized-GQDs and MPc-Au@Ag conjugate. The probe could detect, in a sequential manner, Hg²+ and biothiols with high sensitivity. Results obtained from the LODs of the probes showed that GQDs sensing performances could be enhanced in the presence of MPcs. The probes designed in this work were successfully deployed in the assays of the target analytes in real samples and the recoveries obtained confirmed the analytical applicability of the probes.
Keywords: Quantum dots; Graphene; Phthalocyanines; Nanoconjugates; Novel photoluminescent nanosensors; Metallophthalocyanines